Pengaruh Skeptisme, Pengalaman Auditor Dan Self-Efficacy Terhadap Audit Judgement Dengan Time Pressure Sebagai Variabel Moderating Pada Badan Pemeriksa Keuangan (BPK) Provinsi Sumatera Utara - Ashadi, Riza; Sari, Eka Nurmala; Astuty, Widia (CV. ITTC INDONESIA, 2024)
The financial report opinion with the title of Unqualified (WTP) Opinion from the Supreme Audit Agency (BPK) for the 2023 Regional Government Financial Report (LKPD) and is the 10th consecutive WTP Opinion obtained by the North Sumatra Provincial Government since 2015. The opinion results from BPK are interesting to study further because the North Sumatra Provincial Government received an Unqualified Opinion (WTP) but there is still a lot of corruption or fraud within the North Sumatra Provincial Government. This is a real phenomenon that occurs in the Government of North Sumatra Province. Providing an audit opinion on the Local Government Financial Statements is based on an audit judgment made by an auditor, with reference to the following aspects: (a) Conformity with Government Accounting Standards (SAP); (b) Effectiveness of Internal Control; (c) Compliance with statutory provisions; and (d) Full Disclosure. There are several factors that can affect audit judgment, namely pressure, auditor experience, professional skepticism and self-efficacy. The type of research that will be used to analyze this research is a quantitative type with an associative type of approach that analyzes data in the form of numbers and then discusses it through the calculation of the score or value of each variable, then proceeds with statistical analysis carried out with the help of the SEM PLS program to prove the influence between the observed variables. The sample in this study were 64 auditors at the Supreme Audit Agency (BPK) of North Sumatra Province. The data was processed using the SEM method with Smart PLS 3.0 software. The results of this study indicate that skepticism affects audit judgment, auditor experience affects audit judgment, self efficacy affects audit judgment, skepticism affects audit judgment moderated by time pressure, auditor experience affects audit judgment moderated by time pressure, audit judgment affects audit judgment moderated by time pressure.